Conceptual framework of coaches’ decision-making in conventional sports - Kolar, Edvard; Biloslavo, Roberto; Pišot, Rado; Veličković, Saša; Tušak, Matej (Frontiers in Psychology, 2025)
IntroductionA coach’s managerial and pedagogical tasks in the sports training process constitute the substantive core of their work, while decision-making serves as the fundamental method underpinning these tasks. Some decisions made by coaches result from deliberate, analytical thinking, which involves extensive information gathering, analysis, and discussion. Others, however, are made quickly and spontaneously, triggered by unforeseen situations during training or competition that demand immediate action. Consequently, the purpose of this study is to develop a conceptual framework for understanding coaches’ decision-making behavior in conventional sports. This framework aims to establish appropriate relationships between the various decisions coaches make during the training process and theoretical concepts related to decision-making, both in general and within the coaching context.MethodsTo design the research, we used the methodology of a conceptual paper and a “model paper” approach, which seeks to build a theoretical framework that predicts relationships between distinct research concepts and scientific disciplines, aiming to integrate them into a cohesive model of coaches’ decision-making behavior.ResultsThe proposed conceptual framework encompasses a comprehensive range of situations that may arise during the sports training process and potential ways to address them. This framework identifies different types of decisions and characteristics associated with coaches’ decision-making behavior. It incorporates various sport-specific and general theories of decision-making and cognitive functioning to offer a deeper understanding of how coaches process and execute decisions in diverse contexts.DiscussionThe developed conceptual framework outlines three primary types of decisions—strategic, tactical, and operational—each playing a distinct role in the broader sports training process. These decisions are based on different cognitive processes, which manifest in varied decision-making behaviors and are reinforced by specific leadership styles. The practical value of this framework lies in its potential application for selecting appropriate experts to address the diverse decision-making scenarios encountered in sports training. This ensures the alignment of decision-making styles with the requirements of specific training situations, thereby enhancing the effectiveness and outcomes of the coaching process.